Epigenetic control of plant regeneration: Unraveling the role of histone methylation - Saikat Sena; Ajit Prakash; Johannes Van Staden; Vijay Kumar (Current Plant Biology)
It is incredible that plants can actively promote cellular dedifferentiation and regeneration. The change in cell fate is accompanied by modifications to the epigenetic landscape. Plants may regulate developmental processes and environmental adaptation via the establishment, maintenance, and removal of epigenetic changes in addition to genetically encoded variables. Studies on plant regeneration are very important since the underlying processes are connected to basic research in many different domains as well as the development of widely used plant biotechnology. De novo organogenesis, somatic embryogenesis, and tissue regeneration are the three primary kinds of regeneration observed in higher plants. In-vitro culturing may cause histone methylation to reassemble the nuclear architecture. The process of somatic embryogenesis and regeneration relates to different methylation states that regulate gene expression in-vitro. In order to generate huge amounts of top-notch planting materials or to enhance agronomic features that promote crop development, it may be necessary to change the methylation profile. Enhancing the embryogenic potential and totipotency in resistant plant species and specific genotypes could be achievable by developing techniques with the aid of an understanding of the molecular processes behind methylation changes and the acquisition of embryonic cell destiny during in-vitro cultures. Additionally, the methylation profile may help crops adapt to extreme conditions when they experience diverse challenges throughout in-vitro growth. In this article, we examine the studies on how histone methylation affects plant variety and explore the possibilities of targeted epigenetic modification for crop development.